2020
DOI: 10.1080/08989621.2020.1747019
|View full text |Cite
|
Sign up to set email alerts
|

Toward global standardization of conducting fair investigations of allegations of research misconduct

Abstract: In the United States, through nation-wide discussions, the procedures for handling allegations of research misconduct are now well established. Procedures are geared toward carefully treating both complainants and respondents fairly in accordance with the US framework. Other countries, which have their own cultural and legal framework, also need fair and legally compatible procedures for conducting investigations of allegations of research misconduct. Given the rapid growth of international collaboration in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…These special organizations or working groups, overseeing the development of the allover inquiry and investigation processes, are required to consist of a limited number of researchers by national guidance (Ministry of Education of the People's Republic of China, 2014). Most of our sampled universities' policies utilized a number of measures to protect against conflicts of interest including the use of outside experts, limited terms for committee membership, excluding members of the same organizational unit from inquiry or investigation committees, and/or the use of signed statements for self-disclosure of possible conflicts, and it is consistent with other study (CHPS Consulting, 2000;Nouchi et al, 2020).…”
Section: Ensuring a Fair And Appropriate Investigationsupporting
confidence: 70%
See 1 more Smart Citation
“…These special organizations or working groups, overseeing the development of the allover inquiry and investigation processes, are required to consist of a limited number of researchers by national guidance (Ministry of Education of the People's Republic of China, 2014). Most of our sampled universities' policies utilized a number of measures to protect against conflicts of interest including the use of outside experts, limited terms for committee membership, excluding members of the same organizational unit from inquiry or investigation committees, and/or the use of signed statements for self-disclosure of possible conflicts, and it is consistent with other study (CHPS Consulting, 2000;Nouchi et al, 2020).…”
Section: Ensuring a Fair And Appropriate Investigationsupporting
confidence: 70%
“…In Japan, MEXT conducted a survey on university implementation of the "Guidelines for Responding to Misconduct in Research, " organized a special survey every year, and published the results (Ministry of Education, Culture, Sports, Science and Technology Japan, 2022). The survey inquired in great detail about the university's investigation procedure and committee, initiatives to raise awareness of research ethics, preservation and presentation of research data, and promotion of RI, especially novel and distinctive practices (Nouchi et al, 2020). It also requested that respondents provide evidence such as documents, protocols, names of meetings where decisions were made, and dates of resolutions.…”
Section: Inquiry and Investigationmentioning
confidence: 99%
“…However, research performing organizations may have been unable to investigate allegations against their employees effectively due to a lack of guidelines (National Academies of Sciences, 2017 ; National Academies of Sciences et al, 2016 ), or disinclined to do so to prevent negative consequences of eventual retractions, such as reputational damage and financial loss (Institute of Medicine, 2012 ), leaving their obligation to investigate allegations to be fulfilled by journal authorities. Research performing organizations may have conducted investigations into allegations against their misbehaving employees but subsequently have decided to cover them up (Nouchi et al, 2020 ) by soft-pedalling the severity of confirmed allegations (e.g., Tsukumo et al, 2016 ), producing research misconduct reports with inadequate credibility (Gunsalus et al, 2018 ), or refusing to reveal their investigations (Abdi et al, 2023 ). As a result, journal authorities may have ended up making retraction decisions based on their own investigations (e.g., The Journal of Rheumatology, 2018 ) to ward off litigations, which can be a plausible explanation for the observed increase in disclosing their investigations into allegations.…”
Section: Discussionmentioning
confidence: 99%
“…The US has set up government agencies to observe institutional investigations. These agencies also have the authority to pass final decisions on cases of misconduct, whereas other countries do not utilize such systems (Matsuzawa, 2014a(Matsuzawa, , 2014b(Matsuzawa, , 2014cNouchi et al, 2020). Scientific misconduct in Japan is handled completely differently from such cases in the US.…”
Section: Introductionmentioning
confidence: 99%